A cross-sectional survey of soil-transmitted helminthiases in two Myanmar villages receiving mass drug administration: epidemiology of infection with a focus on adults - Dunn,JC; Bettis,AA; Wyine,NY; Lwin,AMM; Lwin,ST; Su,KK; Sein,MM; Tun,A; Maung,NS; Anderson,RM (Parasites & Vectors, 2017)
Background: Soil-transmitted helminths (STH) are still highly prevalent in southeast Asia. The country of Myanmarhas had ongoing mass drug administration (MDA) programmes since 2003 in an attempt to control STH andreduce STH-related morbidities. Whilst the MDA programmes have reported high nationwide coverage, therehave been no epidemiological surveys that included measurements from adults. This paper details threecross-sectional surveys that took place over the course of a year in two villages endemic for STH and receivingMDA in lower Myanmar.Results: At baseline, 27.81% of participants were infected with at least one type of STH. The most prevalent STHwas Trichuris trichiura (18.12%) followed by hookworm (8.71%) and Ascaris lumbricoides (5.34%). Most infectionswere of low intensity, measured by eggs per gram of faeces (EPG). Gender stratification revealed that A.lumbricoides prevalence was significantly higher in females, whereas hookworm prevalence was significantlyhigher in males. The distribution of EPG in the study sample was highly overdispersed, suggesting that mostpeople release few eggs whereas a few people release many eggs. Adults harbour a major proportion of theoverall STH burden; 65.15% of STH infections were harboured by adults.Conclusions: STH infection remains at medium prevalence in the study villages despite past and recent MDA.Recorded prevalence of STH in school-aged children has not substantially decreased since the last monitoringand evaluation activities in Myanmar in 2013. Analyses suggest that adults are a major contributor to the totalSTH prevalence and EPG burden, probably perpetuating transmission.